2011 16th International Solid-State Sensors, Actuators and Microsystems Conference 2011
DOI: 10.1109/transducers.2011.5969554
|View full text |Cite
|
Sign up to set email alerts
|

Anodically-bondable LTCC substrates with novel nano-structured electrical interconnection for MEMS packaging

Abstract: In this study, anodically-bondable LTCC (low temperature cofired ceramic) substrates are proposed to provide electrical connective packaging by using novel nano-structured gold. On-chip MEMS compatible fabrication of nanoporous gold (NPG) was developed and its porous structure offers sponge-like functions which forms electrical contacts as well during anodic bonding. A MEMS integrated Si substrate is mechanically sealed to a metal feedthrough LTCC substrate by anodic bonding and its electrical connection is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The ligament sizes of the sheet surface increased with increasing temperature. These results indicated that metal diffusions of Au and Ag occurred even at low temperature because of the high reactive surface of the powders [7,8]. Figure 7 shows the bonding strengths measured by tensile tests.…”
Section: Changes In the Nanoporous Structures Of Powdermentioning
confidence: 95%
See 2 more Smart Citations
“…The ligament sizes of the sheet surface increased with increasing temperature. These results indicated that metal diffusions of Au and Ag occurred even at low temperature because of the high reactive surface of the powders [7,8]. Figure 7 shows the bonding strengths measured by tensile tests.…”
Section: Changes In the Nanoporous Structures Of Powdermentioning
confidence: 95%
“…The use of nanoporous structures on the surface is one of the efficient methods, due to sponge-like flexible features and highly reactive surface of the nano-or mesoscale structures. Since nanoporous structures have a large surface-to-volume ratio, they have been widely used in various applications in sensors, actuators, and clean-energy devices [6,7]. For example, the electrical connective packaging by using nanoporous gold pads was reported [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process for packaging using LTCC with the metal feed-through offers great potential to reduce cost and improve reliability. The simple and versatile technology for hermetic packaging of RF MEMS fabricated by standard anodic bonding process has been reported [7][8]. Fabrication of a silicon diaphragm capacitive pressure sensor for high temperature application using LTCC substrate has been developed [9].…”
Section: Introductionmentioning
confidence: 99%